THE IMPORTANCE OF THE ENVIRONMENT THAT DEVELOPS CHILDREN IN THE PREPARATION FOR SCHOOL EDUCATION IN THE ORGANIZATION OF PRESCHOOL EDUCATION - Ganieva Vazira Yusufovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this article covers the state requirements for the development of early and preschool children of the educational process in preschool educational organizations and the idea of planning on the basis of the state program “first step”.